Production of concrete expansive agents from freshwater sludge and carbide sludge - Mingqian Yang; Bo Xu; Jiawei Tan; En-Hua Yang; Yaolin Yi (Case Studies in Construction Materials, 2025)
Calcium sulfoaluminate-based expansive agents (EAs) can effectively reduce shrinkage in concrete. However, conventional EA production consumes substantial quantities of non-renewable resources, which is costly and not sustainable. This study explores the feasibility of producing cost-effective calcium sulfoaluminate-based EAs from two industrial by-products/wastes, freshwater sludge (FS) and carbide sludge (CS). Different calcination temperatures (1100°C and 1300°C), calcination durations (1, 2, and 3 h), and CaO/Al2O3 ratios (4 and 5) were considered for the production of EAs. The physical, chemical, and microstructural properties of the FS-CS-made EAs were examined. The performance of cement with and without EAs was subsequently analyzed, including restrained expansion, compressive strength, flexural strength, and setting time. Finally, the hydrated phases of cement blended with EAs were analyzed. Results showed that the FS-CS-made EAs mainly consisted of ye'elimite, mayenite, anhydrite, and calcium oxide, similar to conventional EAs. Cement mortar without EAs displayed continuous shrinkage, resulting in a shrinkage value of 0.030 % at 28 days. Cement blended with 10 % FS-CS-made EA showed a rapid expansion tendency within the initial 3–4 days, reaching a maximum restrained expansion of 0.038 %. The achieved 7-day and 28-day restrained expansion values met the required standards. All in all, this study demonstrates FS and CS can be used as ingredients for the production of calcium sulfoaluminate-based EAs. This approach reduces the consumption of non-renewable resources, increases the value of waste materials, and provides a sustainable solution for waste management.